2013
DOI: 10.7732/kjpr.2013.26.3.355
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Abeliophyllum distichum Nakai Flower Extracts on Antioxidative Activities and Inhibition of DNA Damage

Abstract: -The present study attempts to evaluate antioxidant activities of extracts from Abeliophyllum distichum. Nakai flower. The samples were collected in Jangyyeon-myeon, Goesan-gun, Korea and extracted with either hot-water or ethyl acetate (EtOAC). In DPPH, hydroxyl radical scavenging activity and Fe 2+ chelating activity of EtOAC extracts were 93.41%, 98.43%, and 7.38%, while those of hot-water extracts were 86.93%, 41.33% and 47.68% at 200 μg/ml, respectively. In φX-174 RF I plasmid DNA cleavage assay, the prot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
9
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 21 publications
0
9
0
1
Order By: Relevance
“…Additionally, the effects of the antioxidant properties of AAD on oxidative DNA damage were also examined. Our previous studies suggested that A. distichum had potential antioxidant activities ( 49 , 50 ). DPPH and ABTS radicals are the most common and most stable chromogens used to estimate antioxidant activity of biological materials.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, the effects of the antioxidant properties of AAD on oxidative DNA damage were also examined. Our previous studies suggested that A. distichum had potential antioxidant activities ( 49 , 50 ). DPPH and ABTS radicals are the most common and most stable chromogens used to estimate antioxidant activity of biological materials.…”
Section: Discussionmentioning
confidence: 99%
“…Phytochemical studies have identified two phenylethanol glycosides: verboscoside (acteoside) and arenarioside; two benzoquinolethanoids: cornoside and halleridone; and a lignin glucoside, epipinoresinol 4 0 -O-glucoside 3,4 . Some of these compounds have been reported as having antioxidant, anti-angiotensin and antidiabetic properties 2,5 . However, the compounds responsible for its anti-inflammatory actions remain elusive.…”
Section: Introductionmentioning
confidence: 99%
“…Phytonutrients used for food, cosmetic and pharmaceutical products not only have negligible amount of poison to our body, but also have strong biological activity (Ahn and Park, 2013). Most free radicals, being known as reactive oxygen species (ROS) and reactive nitrogen species (RNS) are considered to be a fundamental cause of physiological diseases such as cancer, aging, diabetes mellitus, Alzheimer's disease and coronary heart ailment (Bulkley, 1983;Cheng et al, 2003;Finkel and Holbrook, 2000).…”
Section: Introductionmentioning
confidence: 99%